The Financial Wellness Industry and a Crowded Legal‐Employment Market: Market Failure Summons Synergy. (June 2015) - Steven Swan, George
<x xml:space="preserve">Abstract</x> A mismatch between meager job openings for attorneys and a years‐long eruption of law school graduates is a concern. By contrast, in 2014, the personal financial planning occupation appeared among the more rapidly growing fields for the timeframe ending in 2020. The law degree marks an asset within the financial planning industry. Personal financial planning overlaps with law in estate planning and income taxation. The purpose of this paper is to suggest for underemployed Juris Doctors that (1) the financial wellness industry possibly affords an opening into the broader arena of financial services; and that (2) the Certified Personal and Family Finance Educator credential awarded by the American Association of Family and Consumer Sciences provides a potential bridge from the law school campus into the financial wellness industry. Research into the feasibility of this pair of propositions is suggested, while potential sources of relevant information are identified.